2017
DOI: 10.1111/ddg.13233
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for silver in wound care – meta‐analysis of clinical studies from 2000–2015

Abstract: The present meta-analysis shows that the evidence base for silver in wound management is significantly better than perceived in the current scientific debate. Thus, if used selectively and for a limited period of time, silver not only has antimicrobial effects but is also characterized by an improvement in quality of life and good cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 48 publications
2
39
0
6
Order By: Relevance
“…Silver has been shown to have an antibacterial effect, and topical silver‐containing treatments (creams, dressings, etc) are widely used for IDFUs. While silver compounds may offer some benefits in ulcer healing, there is little evidence (including from several systematic reviews) to support their effectiveness in treating or preventing ulcer infection . Several small studies have, however, demonstrated anti‐infective benefits for some antiseptic agents (eg, cadexomer iodine and hypochlorous solutions) in infected DFUs.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver has been shown to have an antibacterial effect, and topical silver‐containing treatments (creams, dressings, etc) are widely used for IDFUs. While silver compounds may offer some benefits in ulcer healing, there is little evidence (including from several systematic reviews) to support their effectiveness in treating or preventing ulcer infection . Several small studies have, however, demonstrated anti‐infective benefits for some antiseptic agents (eg, cadexomer iodine and hypochlorous solutions) in infected DFUs.…”
Section: Treatmentmentioning
confidence: 99%
“…To specifically address infection in a diabetic foot ulcer, a) do not use adjunctive granulocyte colony stimulating factor treat- 178 there is little evidence (including from several systematic reviews) to support their effectiveness in treating or preventing ulcer infection. 179 Several small studies have, however, demonstrated anti-infective benefits for some antiseptic agents (eg, cadexomer iodine and hypochlorous solutions) in infected DFUs.…”
Section: Recommendation 27mentioning
confidence: 99%
“…A meta-analysis of 157 clinical studies published from 2000 to 2015 concluded that the evidence base for silver in wound management was significantly more favorable than commonly perceived in the clinical community, with evidence suggesting that the use of silver in wound management is also costeffective and improves the patient quality of life. [26] Amid silver-based antimicrobials, silver NPs are broadspectrum bactericidal and virucidal species. [27] Furthermore, as shown for instance by the AgNPs capped with mercaptoethane sulfonate targeting the herpes virus, [10] they can be tailed to target specific microorganisms by surface functionalization.…”
Section: Advancing Ag-based Antimicrobials and Antiviralsmentioning
confidence: 99%
“…Signs of wound infection include pus, spreading redness, increased pain or swelling, and fever a break in the skin (a wound) shows signs of infection. They includes: infected cuts, scrapes, sutured wounds, puncture wounds and animal bites; most dirty wounds become infected 24 to 72 hours later [21].Caring for child's wound is important to promote healing, avoid infection and minimise scarring. Different types of wounds require different dressing products and care.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of choice remains the penicillinase-resistant penicillins such as cloxacillin and flucloxacillin. In adults, current treatment recommendations are cefazolin or ocloxacillin [25]. Il the elderly many factors may influence the probability of developing an surgical skin infection after a surgical intervention.…”
Section: Discussionmentioning
confidence: 99%